2014
DOI: 10.1097/qad.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endothelin-1 levels and pulmonary arterial hypertension in HIV-infected patients

Abstract: Plasma endothelin-1 levels are higher in HIV patients with PAH than in the HIV-noninfected population and levels increase with the severity of the PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Many factors, as viral proteins, HIV-related inflammation, coinfections with other microrganisms, and genetic susceptibility were considered to contribute to HIV-related PAH. Recently, a direct role of HIV infection to endothelial damage through the release of different inflammatory mediators such as endothelin-1 has been suggested [4]. Even the effect of antiretroviral therapy on pulmonary artery pressure has been an area of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, as viral proteins, HIV-related inflammation, coinfections with other microrganisms, and genetic susceptibility were considered to contribute to HIV-related PAH. Recently, a direct role of HIV infection to endothelial damage through the release of different inflammatory mediators such as endothelin-1 has been suggested [4]. Even the effect of antiretroviral therapy on pulmonary artery pressure has been an area of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…gp120 also increases secretion of another important PAH factor, endothelin-1 (88). Endothelin-1 levels are higher in HIV-seropositive individuals and correlate with HIV-PAH severity (89). …”
Section: Pathogenesis Of Hiv-pahmentioning
confidence: 99%
“…49 A case-control study showed that plasma endothelin-1 levels were elevated in HIV-infected patients and were most elevated in patients with severe HIV-PAH. 50 Both HIV Env and Tat have been shown in vitro to enhance TNF-α-mediated activation of lung microvascular endothelial cells. 51 Mermis and colleagues identified increased expression of hypoxia-inducible factor-1α (HIF-1α) and PDGF-BB in the HIV transgenic rat, and showed in vitro that endothelial cells stimulated with HIV-Env increase PDGF-BB expression, which is abrogated by siRNA blockade of HIF-1α.…”
Section: Direct Effects Of Hiv Viral Proteinsmentioning
confidence: 99%